SOROTAN LITERATUR TERPILIH TENTANG PELAKSANAAN TADBIR URUS YANG BAIK DALAM PENGELUARAN AYAM HALAL DI MALAYSIA DAN ISU BERKAITAN: A Selected Literature Review on the Implementation of Good Governance in Halal Chicken Production in Malaysia and the Related Issues - Razaly, Muhamad Mazuan; Zakaria, Zalina; Syed Ismail, Sharifah Hayaati (Journal of Shariah Law Research, 2023)
Halal industry has become one of the agenda in the development of the nation’s economic growth. Several improvements have been implemented by JAKIM, JAIN or MAIN, as the main authority, to ensure that halal governance runs well including in the production of halal chicken meets the aspects of halalan toyyiban. There are also initiatives taken by other agencies as per their respective jurisdictions. However, issues related to halal chicken continuously arise, and it worries consumers. Thus, the study was conducted to analyse the effectiveness of the governance in the implementation of halal certification between the relevant agencies, and will further suggest the relevant halal governance framework. In order to ensure that the information collection process runs smoothly, this qualitative study uses two important instruments, namely document analysis and interviews involving those experts in the field. Research on these aspects would not complete without going through some reviews on the relevant literature. After making several search where literature sources were obtained, several themes have been formed and have been determined. The themes are: halal governance, issues and challenges of halal governance in Malaysia, legislation in halal governance in Malaysia and lastly good governance.